2001
DOI: 10.1677/joe.0.1710259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eicosapentaenoic acid ethyl ester on hypothyroid function

Abstract: Thyroid hormones affect reactions in almost all pathways of lipid metabolism. It has been reported that plasma free fatty acid (FFA) concentration in hypothyroidism is generally within the normal range. In this study, however, we show that plasma FFA concentration in some hypothyroid patients is higher than the normal range. Symptoms of thyroid dysfunction in these individuals were less severe than those of patients with lower plasma FFA concentrations. From these findings we hypothesized that the change in FF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Moreover, the present study showed that omega-3 treated rats had a significant increase in T3 level and a significant decrease in TSH level as compared to the hypothyroid group. These results agreed with Makino et al (35) who remarked that omega-3 supplementation to hypothyroid rats prevents the decrease in plasma T3 and T4 levels and prevents the increase in TSH level. This may be due to that omega-3 modulates TSH receptor, its binding ability to TSH and adenylate cyclase system (35).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the present study showed that omega-3 treated rats had a significant increase in T3 level and a significant decrease in TSH level as compared to the hypothyroid group. These results agreed with Makino et al (35) who remarked that omega-3 supplementation to hypothyroid rats prevents the decrease in plasma T3 and T4 levels and prevents the increase in TSH level. This may be due to that omega-3 modulates TSH receptor, its binding ability to TSH and adenylate cyclase system (35).…”
Section: Discussionsupporting
confidence: 92%
“…These results agreed with Makino et al (35) who remarked that omega-3 supplementation to hypothyroid rats prevents the decrease in plasma T3 and T4 levels and prevents the increase in TSH level. This may be due to that omega-3 modulates TSH receptor, its binding ability to TSH and adenylate cyclase system (35). The reactive oxygen species (ROS)-mediated oxidative damage was suggested to play an important role in the manifestations of hypothyroidism (39).…”
Section: Discussionsupporting
confidence: 92%
“…A raised plasma concentration of TSH was found in rats fed diets enriched in C22:6 compared with animals on a diet supplemented with AA or a standard diet (Clandinin et al, 1998). Stimulating effects of n-3 polyunsaturated FA have also been observed for other elements of HPT axis activity such as transthyretin expression in the brain (Puskas et al, 2003) and thyrocyte proliferation (Makino et al, 2001). However, other results also suggest the involvement of PUFA n-6 in the stimulation of thyroid activity.…”
Section: Discussionmentioning
confidence: 96%
“…Unsaturated fatty acids have been shown to possibly prevent hypothyroidism. [71] The thyroidic activity of argan oil has been evaluated in a cohort study performed on 149 euthyroidic volunteers consuming non-iodised salt by measuring plasmatic concentrations of free tri-iodothyronine (FT3), tetra-iodothyronine (FT4) and thyroid stimulating hormone. This study evidenced that no activity on hypothyroidism could be expected from argan oil dietary supplementation.…”
Section: Influence On Thyroid Hormone Profilementioning
confidence: 99%